Numerical investigation of stress concentration and deformation behavior of steel I-beams with web openings using the finite element method - Nguyen, Huu-Dien (International Journal of Chemical and Process Engineering Research, 2026)
Steel I-beams with web openings are widely used in modern steel structures to accommodate mechanical and electrical services and improve construction efficiency. However, web openings alter the internal force transfer mechanism of the beam, leading to stress concentration and increased deformation, which may affect structural safety and serviceability. This study presents a numerical investigation of the stress distribution and deformation behavior of steel I-beams with web openings using the Finite Element Method (FEM). Three-dimensional finite element models of IPE steel beams are developed in ANSYS, incorporating elastic–plastic material behavior and geometric nonlinearity. Beams with different web configurations, including solid webs, circular openings, and square openings with equivalent areas, are analyzed under four-point bending. The effects of opening geometry on stress concentration, mid-span deflection, and overall structural response are examined. The numerical results show that the presence of web openings significantly increases stress concentration and reduces beam stiffness compared to solid web beams. Circular openings produce a more uniform stress distribution with lower peak stresses, while square openings lead to higher stress concentration at the corners due to pronounced Vierendeel action. Comparison with analytical solutions for solid beams demonstrates good agreement, confirming the validity of the numerical modeling approach. The findings provide useful insights for the design and assessment of perforated steel beams in practical engineering applications.